Women’s Empowerment Strategies and Family Economic Resilience through MSMEs: A SWOT Analysis - Ridho, Rifki Taufik (LifeSciFi, 2026)
Women’s participation in MSMEs plays a vital role in strengthening household welfare and local economic resilience in Indonesia. This study analyzes women’s empowerment strategies through the Muslimat Nahdlatul Ulama (NU) organization in Bandung City to enhance family economic resilience, focusing on MSMEs. Employing a qualitative approach via case study and SWOT analysis along with IFAS and EFAS matrices, the research identifies external opportunities such as local government policy support, growth in creative MSME sectors, digital technology utilization, societal interest in halal or local products, and partnerships with sharia financial institutions. However, external threats include intense competition in urban MSMEs, economic instability and price fluctuations, rapid technological changes, and dependency on external aid. The results demonstrate that integrating NU’s religious values with empowerment programs effectively strengthens holistic family economic independence. The conclusion emphasizes the need for synergy between micro-financial management and macro support through stakeholder collaboration for sustainability. Recommendations include ongoing mentoring and the establishment of a dedicated coordination institution.